1992
DOI: 10.2105/ajph.82.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, disability, and falls in older persons: the role of underlying disease and disability.

Abstract: BACKGROUND. Falls are prevalent in older persons and can have serious consequences. METHODS. Data from the Longitudinal Study on Aging were analyzed to study the relationship between falls and both mortality and functional status in 4270 respondents age 70 and over. The effects of demographic traits, chronic conditions, and disability present at baseline were controlled for by means of multivariable analyses. RESULTS. Risk of death within 2 years was greater for both single fallers (crude odds ratio [OR], 1.5;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
89
2
6

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(103 citation statements)
references
References 15 publications
6
89
2
6
Order By: Relevance
“…Donald and Bulpitt [36] showed an increased risk of death at the 1- and 3-year follow-up in elderly non-uremic subjects over 75 years of age for ‘recurrent fallers’ but not for ‘single fallers’. Similarly, Dunn et al [37] showed a 2.2-fold increase risk for death in ‘recurrent fallers’ versus only 1.5-fold for ‘single fallers’.…”
Section: Discussionmentioning
confidence: 96%
“…Donald and Bulpitt [36] showed an increased risk of death at the 1- and 3-year follow-up in elderly non-uremic subjects over 75 years of age for ‘recurrent fallers’ but not for ‘single fallers’. Similarly, Dunn et al [37] showed a 2.2-fold increase risk for death in ‘recurrent fallers’ versus only 1.5-fold for ‘single fallers’.…”
Section: Discussionmentioning
confidence: 96%
“…In a community based cross sectional study it has been shown that from one-fourth up to one-third of the persons 65 years or older reported a fall in the previous year [2,3]. In the elderly, between 10 % and 15 % of the falls result in serious injury and between 5 % and 10 % cause a fracture [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the elderly, approximately 1 to 3 percent of falls results in a hip fracture, and over 90 percent of hip fractures are caused by a fall (4)(5)(6). Falls also may lead to various other types of fractures, soft tissue injury, head traumas, and increased mortality (7,8). The cumulative incidence of falling among elderly people varies between 30 percent and 50 percent over a 1-year period (6,(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%